LEGAL REGULATION OF LABOUR RELATIONS WITH THE EMPLOYEES MOBILIZED TO THE ARMED FORCES OF UKRAINE - Kmetyk, Khrystyna; Shyian, Yuliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The hostilities that take place in the East of Ukraine for more than eight years have become an extremely difficult test for the Ukrainian people and the Ukrainian state. A significant number of citizens were mobilized to the Armed Forces of Ukraine in order to protect the territorial integrity of Ukraine. However, on February 24 last year, Ukraine faced a new challenge from the russian federation. The full-scale invasion of the aggressor country on our lands led to the mobilization of thousands of the employees of enterprises, institutions and organizations to the Armed Forces of Ukraine. The war created an unprecedented number of new problems and challenges for citizens and society as a whole. Many problems have arisen related to the economy, medical care, housing and other socially important issues that concern every Ukrainian. One of these critically important issues is the legal regulation of labour relations with the employees who were mobilized for military service. Purpose: to research the main legal principles of implementing the legal regulation of labour relations with the mobilized employees in Ukraine. Research methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive and analytical, etc. Results: the main legal principles of implementing the legal regulation of labour relations with the mobilized employees in Ukraine are characterized and defined. Discussion: the authors consider and analyse the labour relations with the employees mobilized to the Armed Forces of Ukraine, which are regulated by special legislation and normative acts of Ukraine, which determine the procedure for conscription for military service and dismissal from it, employment conditions after returning from military service, guarantees of labour rights and social protection of the mobilized employees. It has been established that the legal regulation of labour relations with the mobilized workers, who were called during mobilization to the Armed Forces of Ukraine, is undoubtedly a complex issue that requires attention from the legal community to ensure effective protection of the rights and interests of such employees. To achieve this goal, it is important the unity and cooperation of all members of society, since the protection of the sovereignty and territorial integrity of Ukraine is one of the most important tasks of the Ukrainian people.